Awareness of breast cancer attitude and practice of screening among female support staff. - Thapa,Savina (2020)
ABSTRACT: Introduction: Breast cancer is the most common cancer among women worldwide. In developing countries, mortality from breast cancer is higher than developed countries due to low level of knowledge and poor practice of breast cancer screening. The aim of this study is to assess the awareness of breast cancer, attitude and practice of its screening among female support staff. Method: A cross sectional analytical study carried at Patan Academy of Health Sciences, among 127 female support staff by total enumerative sampling techniques were interviewed using a structured questionnaire. Data analysis was done using SPSS version 16. Descriptive statistics such as frequency and percentage were used to analyze the level of awareness, attitude and practice. The relationship between awareness and practice, attitude and practice were analyzed using Spearman's correlation co-efficient. Results: 64.57% of respondents had poor, 28.35% had average and 7.14% had good level of awareness regarding breast cancer and screening. 52.76% of the respondents had favorable and 47.24% had unfavorable attitude of screening practice. 37% of respondents performed of breast cancer screening methods. There was significant correlation (r =.313, p = .032) between awareness and practice whereas there was no correlation (r = -.045, p= .726) between attitude and practice. Conclusions: There was one- fourteenth had good level of awareness of breast cancer. More than half of respondents had favorable attitude and one- twelfth of respondents had good practice of breast cancer screening. There was significant weak positive correlation between awareness and practice. Educational intervention will be needed for female support staff, that helps to increase the awareness and practice of breast cancer screening. Keywords: Attitude, Awareness, Breast Cancer, Female Support Staff, Screening Practice.